2021
DOI: 10.1177/14613557211064050
|View full text |Cite
|
Sign up to set email alerts
|

A national study of the availability of law enforcement agency wellness programming for officers: A latent class analysis

Abstract: The purpose of this study is to understand the availability of employee wellness programs within law enforcement agencies (LEAs) across the United States, including physical fitness, resilience/wellness, coping skills, nutrition, mental health treatment, and substance use treatment. The research team investigated whether patterns of LEA wellness programming are identifiable and, if so, what characteristics describe these patterns. We assess using latent class analysis whether there are distinct profiles of age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…Worksite wellness programs have been shown to have beneficial impacts on the mental and physical health of (LEO’s) (Acquadro Maran et al, 2018; Antony et al, 2020; MacMillan et al, 2017; Taylor et al, 2021). Nevertheless, most law enforcement agencies do not currently offer wellness programs (Taylor et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Worksite wellness programs have been shown to have beneficial impacts on the mental and physical health of (LEO’s) (Acquadro Maran et al, 2018; Antony et al, 2020; MacMillan et al, 2017; Taylor et al, 2021). Nevertheless, most law enforcement agencies do not currently offer wellness programs (Taylor et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Worksite wellness programs have been shown to have beneficial impacts on the mental and physical health of (LEO’s) (Acquadro Maran et al, 2018; Antony et al, 2020; MacMillan et al, 2017; Taylor et al, 2021). Nevertheless, most law enforcement agencies do not currently offer wellness programs (Taylor et al, 2021). Although previous studies have assessed the impact of some occupation-specific risk factors on the health of LEO’s, few have involved LEO’s as participants in ways that allow their point of view to be heard directly.…”
Section: Introductionmentioning
confidence: 99%
“…Whether agency-provided or external, officers experiencing psychological distress were accessing between one and three services. It should be acknowledged that recent research undertaken by Taylor et al (2022) using agency level analysis found that 62% of U.S. agencies did not offer wellness services. The findings of both the current research and Taylor et al (2022) point to the importance of understanding availability at the agency level.…”
Section: Discussionmentioning
confidence: 99%
“…It should be acknowledged that recent research undertaken by Taylor et al (2022) using agency level analysis found that 62% of U.S. agencies did not offer wellness services. The findings of both the current research and Taylor et al (2022) point to the importance of understanding availability at the agency level. In addition, the present research highlights the importance of the proportion of officers in the law enforcement population who have services available to them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation